2020
DOI: 10.1128/jvi.02177-19
|View full text |Cite
|
Sign up to set email alerts
|

Concurrent Control of the Kaposi's Sarcoma-Associated Herpesvirus Life Cycle through Chromatin Modulation and Host Hedgehog Signaling: a New Prospect for the Therapeutic Potential of Lipoxin A4

Abstract: Lipoxin A4 (LXA4) is an endogenous lipid mediator with compelling anti-inflammatory and proresolution properties. Studies done to assess the role of arachidonic acid pathways of the host in Kaposi's sarcoma-associated herpesvirus (KSHV) biology helped discover that KSHV infection hijacks the proinflammatory cyclooxygenase-2 (COX-2) and 5-lipoxygenase (5-LO) pathways and concurrently reduces anti-inflammatory LXA4 secretion to maintain KSHV latency in infected cells. Treatment of KSHV-infected cells with LXA4 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 69 publications
(83 reference statements)
0
18
0
1
Order By: Relevance
“…Mass spectrometry analysis from our experiment also suggested LXA4 be interacting with factors associated with metabolic and signaling pathways, immune response, cell proliferation, angiogenesis, transport-related proteins, and nuclear protein related to KSHV replication and life cycle ( Asha et al., 2020 ). In the study, we identified that during the KSHV infection, RTA (replication and transcription activator) protein regulating the latent-lytic switch, recruits SWI/SNF chromatin remodeling complex and other cofactors to the viral promoter to facilitate RTA dependent KSHV gene expression.…”
Section: Introductionmentioning
confidence: 69%
See 2 more Smart Citations
“…Mass spectrometry analysis from our experiment also suggested LXA4 be interacting with factors associated with metabolic and signaling pathways, immune response, cell proliferation, angiogenesis, transport-related proteins, and nuclear protein related to KSHV replication and life cycle ( Asha et al., 2020 ). In the study, we identified that during the KSHV infection, RTA (replication and transcription activator) protein regulating the latent-lytic switch, recruits SWI/SNF chromatin remodeling complex and other cofactors to the viral promoter to facilitate RTA dependent KSHV gene expression.…”
Section: Introductionmentioning
confidence: 69%
“…Ex vivo studies have established romidepsin as an effective inhibitor that works against lymphoproliferative diseases ( Smolewski and Robak, 2017 ) and is a better agent for viral reactivation ( Wei et al., 2014 ) than other HDAC inhibitors. Likewise, a recent study from our lab has shown anti-inflammatory lipoxin A4 (LXA4) as a promising candidate for lytic induction therapy ( Asha et al., 2020 ). LXA4 treatment regulates KSHV reactivation and life cycle through chromatin modification ( Asha et al., 2020 ) and the host’s hedgehog signaling pathway ( Asha et al., 2020 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, it has been reported that LXA4 binds to the nuclear aryl hydrocarbon receptor (AhR) (Fig. 2 ) (Asha et al 2020 ).…”
Section: Spms Receptorsmentioning
confidence: 99%
“…For example, among SPMs, LXA4 modulates Kaposi’s Sarcoma-Associated Herpesvirus (KSHV) life cycle through chromatin modulation and hedgehog signalling to destabilize the latency of herpes virus and decreases the expression of programmed death-ligand 1 (PD-L1) in Kaposi’s Sarcoma, thereby reducing immune evasion (Fig. 3 ) (Asha et al 2020 ). On the other hand, there are not a few reports that the receptors mentioned above for SPMs act as receptors in virus infection (see below).…”
Section: Role Of Spms and Their Receptors In Virus Infectionsmentioning
confidence: 99%